Use of television, videogames, and computer among children and adolescents in Italy - Marinelli Paolo; Albano Luciana; Di Giuseppe Gabriella; Patriarca Alessandro; Angelillo Italo F (BMC Public Health, 2009)
Abstract Background This survey determined the practices about television (video inclusive), videogames, and computer use in children and adolescents in Italy. Methods A self-administered anonymous questionnaire covered socio-demographics; behaviour about television, videogames, computer, and sports; parental control over television, videogames, and computer. Results Overall, 54.1% and 61% always ate lunch or dinner in front of the television, 89.5% had a television in the bedroom while 52.5% of them always watched television there, and 49% indicated that parents controlled the content of what was watched on television. The overall mean length of time daily spent on television viewing (2.8 hours) and the frequency of watching for at least two hours per day (74.9%) were significantly associated with older age, always ate lunch or dinner while watching television, spent more time playing videogames and using computer. Those with parents from a lower socio-economic level were also more likely to spend more minutes viewing television. Two-thirds played videogames for 1.6 daily hours and more time was spent by those younger, males, with parents that do not control them, who watched more television, and who spent more time at the computer. The computer was used by 85% of the sample for 1.6 daily hours and those older, with a computer in the bedroom, with a higher number of computers in home, who view more television and play videogames were more likely to use the computer. Conclusion Immediate and comprehensive actions are needed in order to diminish time spent at the television, videogames, and computer.